Inflammatory pseudotumour of skull base – Diagnostic challenge and treatment outcome - Abdullah, Kahairi; Raja Lope Ahmad, Raja Ahmad Al'konee; Wan Leman, Wan Ishlah; Harun, Norra (Malaysian Medical Association, 2012)
We report a case of an inflammatory pseudotumour (IP) involving the floor of the skull base, which demonstrated aggressive behavior both clinically and radiologically. In this case, the diagnosis was established by clinical presentation, magnetic resonance imaging (MRI), histopathological examination (HPE) and the dramatic response towards high dose steroid therapy. The clinical features improved with oral cyclophosphamide in combination with oral steroid, which were given for a period of three months.